Die Entropiekonzept zur Ermittlung räumlicher Eigenschaften von innerstädtischen Wanderungsverflechtungen am Beispiel Ludwigshafen/Rhein - Gans, Paul (ERDKUNDE, 1979)
This paper examines migratory inter-weaving at the inner-city level between the urban districts of Ludwigshafen-on-Rhine during the years1973, 1975 and 1977 by the application of entropy to the conditional probability of immigration and emigration, as well as of the comparison of migration figures actually available and those estimated on the basis of marginal totals. They show that the residential preferences of the population are limited to nearby parts of the town, and that there are hardly any connections between spatially isolated sub-areas of the town. These results are supported by the inclusion of continuity in time of the existence of residential preferences at the level of sub-areas, as well as districts, of the town, and an attempt is made to explain them taking a behavioural and decision-taking theoretical approach.